The effect of octreotide on peritoneal alterations induced by high concentration of glucose - Gunal, AI; Gezen, M; Ozercan, R; Oner, H; Celiker, H (Multimed Inc, 1998)
[Abstract Not Available]
Keywords: Somatostatin Analogs; Mesothelial Cells; Expression; Tgf-Beta-1; Dialysis; Growth